O relacjach kategorii „deiktyczności” i „fasadowości” - Горбунова, Людмила (Studia Rossica Posnaniensia, 2016)
This paper deals with the categories spatial deixis, observer, front. We distinguish two types of observer: Observer-speaker and Collective observer. Collective Observer is a necessary semantic category to understand the meanings of some linguistic units adequately. These units reflect the language community's understanding of what kind of orientation towards a particular object should be regarded as standard. Using language tools with locative semantics, the speaker applies different spatial strategies.  The category of observer is required for all of these.